High‐intensity interval training using whole‐body exercises: training recommendations and methodological overview - Machado, Alexandre F.; Baker, Julien S.; Figueira Junior, Aylton J.; Bocalini, Danilo S. (Clinical physiology and functional imaging, 2019)
Summary HIIT whole body (HWB)‐based exercise is a new calisthenics exercise programme approach that can be considered an effective and safe method to improve physical fitness and body composition. HWB is a method that can be applied to different populations and ages. The purpose of this study was to describe possible methodologies for performing physical training based on whole‐body exercise in healthy subjects. The HWB sessions consist of a repeated stimulus based on high‐intensity exercise that also include monitoring time to effort, time to recuperation and session time. The exercise intensity is related to the maximal number of movements possible in a given time; therefore, the exercise sessions can be characterized as maximal. The intensity can be recorded using ratings of perceived exertion. Weekly training frequency and exercise selection should be structured according to individual subject functional fitness. Using this simple method, there is potential for greater adherence to physical activity which can promote health benefits to all members of society.